REFLECTIONS ON TERRITORIAL CLEANSING: LESSONS FROM BOSNIA-HERZEGOVINA AND COLOMBIA (Glocalism: Journal of Culture, Politics and Innovation, 2024)
This small-N cross-regional analysis examines the link between extreme but far from isolated massacres perpetrated during the Bosnian war 1992-1995 and the 1997-2003 interval in the Colombian armed conflict. The afflicted territories by this form of violence underwent a reconfiguration in their demographics in the aftermath of mass killings, forced evictions, disappearances, and displacement. Despite condemning these acts in ad hoc international criminal courts and national tribunals, the question of the dispossessed and their right to return has always been a challenge. This article is based on documentary research to present a comparative overview of the two selected cases employing Egbert et al. (2016) and Lichtenheld’s (2020) territorial cleansing framework to unveil the interconnectedness between the practices and strategies undertaken in Bosnia-Herzegovina and Colombia to contribute to the scholarly work bridging a converging geopolitical perspective within outwardly unrelated episodes of mass political violence.
Keywords: Bosnian War; Colombian armed conflict; territorial cleansing framework; mass political violence; comparative analysis